EDUKASI KEKURANGAN ENERGI KRONIK PADA IBU HAMIL SEBAGAI UPAYA PENURUNAN ANGKA STUNTING DI NAGARI SULIT AIR KABUPATEN SOLOK - Renny Eka Putri; Angela Fortuna Sekarini; Rahmi Dwi Putri; Alifa Azanisya Azzahra; Vasya Azzahra Siona; Roy Saputa; Gizhella Mulyani Putri; Kemal Muhammad Hiero (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Stunting is still a nutritional problem in Indonesia. The main risk factor for stunting is CED (Chronic Energy Deficiency). Education about chronic energy deficiency in pregnant women has an important role in efforts to reduce stunting rates. This programme aims to evaluate the effectiveness of educational programs related to Chronic Energy Deficiency (KEK) in pregnant women as an effort to reduce stunting rates in Nagari Tulis Air, Solok Regency. The research method used is through questionnaires, observation and anthropometric measurements. Data analysis was carried out using appropriate statistical tests. The research results show that the KEK education program has the potential to increase the knowledge and behavior of pregnant women regarding nutrition, as well as reduce the incidence of KEK and stunting. These findings show the importance of the KEK education program in efforts to prevent stunting in areas with nutritional problems such as Nagari Tulis Air, Solok Regency. Recommendations are given to continue and expand the KEK education program and increase the accessibility of health and nutrition services in the area to reduce stunting rates and improve the welfare of pregnant women and children in the future. Educational activities for pregnant women are carried out using the lecture method. Before being presented with the material, the target is first given a pre-test of 10 questions to measure initial knowledge. Then, educational material is given and a post-test is carried out where the questions are the same as the pre-test which aims to see the increase in knowledge after being given education. Based on the pre and post-test results, it was found that the level of knowledge increased by 17%. A better understanding of nutrition and CED in pregnant women has an impact in shaping the views and behavior of pregnant women as an effective strategy in reducing cases of births of children with stunting conditions.